L'Art corporel - Pluchart, François; Galerie Stadler, Paris (Paris : Editions Rodolphe Stadler, 1975)
Duchamp, Marcel ; Manzoni, Piero ; Klein, Yves ; Brus, Günter ; Muehl, Otto ; Nitsch, Hermann ; Rainer, Arnulf ; Schwarzkogler, Rudolf ; Rinke, Klaus ; Nauman, Bruce ; Journiac, Michel ; Oppenheim, Dennis ; etc.
L'Art corporel, à l'occasion d'une exposition à la Galerie Stadler, Paris
Frans & Engels
boek